Examining instructional practices in Core-Plus lessons: implications for professional development - Arbaugh, Fran; Lannin, John; Jones, Dustin L.; Park-Rogers, Meredith (Journal of Mathematics Teacher Education, 2006)
In the research reported in this article, we sought to understand the instructional practices of 26 secondary teachers from one district who use a problems-based mathematics textbook series (Core-Plus). Further, we wanted to examine beliefs that may be associated with their instructional practices. After analyzing data from classroom observations, our findings indicated that the teachers’ instructional practices fell along a wide continuum of lesson implementation. Analysis of interview data suggested that teachers’ beliefs with regard to students’ ability to do mathematics were associated with their level of lesson implementation. Teachers also differed, by level of instructional practices, in their beliefs about appropriateness of the textbook series for all students. Results strongly support the need for professional development for teachers implementing a problems-based, reform mathematics curriculum. Further, findings indicate that the professional development be designed to meet the diverse nature of teacher needs.
Keywords: Core-Plus; Mathematics Education; Philosophy of Education; Professional development; TEACHING; curriculum implementation; instructional practices; secondary mathematics teachers; teacher education